Redescription of the cockroachoid Archimylacris acadica Scudder 1868, key species of the family Archimylacridae, with description of a new specimen from the early Moscovian (Pennsylvanian) of Canada - Schneider, Joerg W.; King, Olivia A.; Stimson, Matthew R.; Béthoux, Olivier; Allen, Luke F.; Norrad, Rowan E.; Malay, Bailey C.; Smith, Lucy L.; Bohus, Caleb P.W.; Hinds, Steven J.; Park, Adrian F. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2026)
The species Archimylacris acadica Scudder, first described from Nova Scotia (Canada), is the type species of the genus Archimylacris and the family Archimylacridae. It is re-described based on historical drawings and a coeval new specimen from the same geographic area, the Maritimes Basin of eastern Canada from Robertson Point (Sunbury Creek Formation) in central New Brunswick. A precise diagnosis of the genus and the species and an emended diagnosis of the family Archimylacridae are given. This new specimen and the type specimen of Archimylacris lubnensis are proposed as reference specimens for the missing holotype of Archimylacris acadica. Paleobiogeographically and stratigraphically, archimylacrids appeared suddenly in the fossil record of the paralic Appalachian Basin with no evolutionary forerunners yet discovered; they became common in the paralic Variscan foreland basins in northern Europe. They are so far unknown from contemporaneous entomofaunas of Cathaysia, from the Angara biotic province, and from Gondwana.